2016
DOI: 10.4149/av_2016_03_298
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity reduces the production of influenza vaccine-induced antibodies via impaired macrophage function

Abstract: Obesity is a metabolic disease characterized by low-level chronic inflammation. Obese individuals are susceptible to infection by viruses, and vaccination against these pathogens is less effective than in nonobese individuals. Here, we sought to explore the immunological environment in a mouse model of obesity induced by a high-fat diet (HFD). HFD treatment increased the body weight and epididymal fat mass. The proportion of activated B cells, T cells, and macrophages was similar between mice in the HFD group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
(21 reference statements)
2
15
0
Order By: Relevance
“…The expressions of CD86 were reduced in adipose tissue macrophages in HFD mice, which in turn causes more inflammatory macrophages infiltration 44 . Consistent with previous studies in adipose tissue 41 , 45 , we observed that the expression levels of CD86 in alveolar macrophages were decreased in HFD mice lungs as compared to RCD mice, which might contribute to the enhanced inflammatory status in HFD mice. We observed that LPS challenge decreased CD86 expressions in alveolar macrophages in RCD mice, which is in accordance with previous study 46 .…”
Section: Discussionsupporting
confidence: 92%
“…The expressions of CD86 were reduced in adipose tissue macrophages in HFD mice, which in turn causes more inflammatory macrophages infiltration 44 . Consistent with previous studies in adipose tissue 41 , 45 , we observed that the expression levels of CD86 in alveolar macrophages were decreased in HFD mice lungs as compared to RCD mice, which might contribute to the enhanced inflammatory status in HFD mice. We observed that LPS challenge decreased CD86 expressions in alveolar macrophages in RCD mice, which is in accordance with previous study 46 .…”
Section: Discussionsupporting
confidence: 92%
“…This deficient antiviral response has been associated with signaling defects in the inflammatory response in mice, leading to high lung inflammation and damage, as well as increased heart inflammation and damage, i.e., increased left ventricular thickness and mass [ 82 ]. A high-fat diet administration in mice has also been associated with an efficacy reduction in influenza vaccine through a reduced antibody response, due to macrophage dysfunction in fatty environments [ 83 , 147 ].…”
Section: Dietary Constituents As Key Factors Of a Strong Immune Symentioning
confidence: 99%
“…The poor vaccine response that is characteristic of the obese host (and is further discussed below) may be partially due to suboptimal macrophage functionality and maturation. Although phagocytosis is increased in peritoneal macrophages isolated from DIO mice, macrophages derived from obese individuals show reduced activation as measured by CD86 expression before and after stimulation ex vivo , impairing their ability to activate effector cells of the immune system (98). This finding is further supported by the increased presence of immature monocytes but equal presence of effector alveolar and interstitial macrophages in BALF collected from DB mice at day 4 p.i (69).…”
Section: Host Antiviral Response To Influenza Infectionmentioning
confidence: 99%